A high stroma-tumor ratio is associated with an immunosuppressive tumor microenvironment and a poor prognosis in bladder cancer - Da, Yiqiang; Lu, Zirong; Zhu, Zijian; Tai, Hongrui; Liu, Yuan; Zhu, Yichao (Frontiers in Oncology, 2025)
PurposeBladder cancer (BLCA) is one of the most common urogenital malignancies in the world. The stroma of the tumor microenvironment (TME) largely affects the progression of BLCA. However, a stroma-relevant biomarker for predicting BLCA progression is still lacking.MethodsWe obtained gene expression profiles and clinical data from the Cancer Genome Atlas (TCGA) datasets via UCSC Xena. The amount of stroma was evaluated using a stromal score and a stroma–tumor ratio (STR). The STR was independently assessed by two pathologists. The stromal score, derived from the R package “ESTIMATE,” was used to calculate the relative proportions of the stroma. We performed cell viability, wound healing, and Boyden chamber assays to determine cell behavior and utilized a BLCA in-house cohort to validate the results of our bioinformatics analysis.ResultsPatients with a higher stromal content showed a worse prognosis. We found that to the high amount of stroma shaped a more immunosuppressive TME in BLCA. Next, we found that stroma could predict molecular subtypes and different therapy options in BLCA. A high stromal content shaped an immune overdrive TME. Cytological experiments revealed that collagen, the main component of the stroma, elevates BLCA cell viability, migration, and invasion. The results from the BLCA in-house cohort also showed that a high stromal content is associated with a worse prognosis and a higher PDL1 expression.ConclusionA high stromal content shapes a more immunosuppressive tumor microenvironment and can predict not only the immune phenotypes but also the clinical phenotypes in BLCA. A high stromal content predicts a worse prognosis. STR exhibits great potential as a biomarker for evaluating the immunogenicity of BLCA and its likelihood of responding to immunotherapy.